2019
DOI: 10.1002/14651858.cd012352.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for reducing morbidity and mortality in malignant melanoma

Abstract: Cochrane Database of Systematic Reviews lasted three years; outcomes were measured at the screening clinics during this time. There was no further follow-up. The purpose of the study was to investigate whether it was possible to conduct a larger trial, which was stopped by lack of funding. The first study was funded by the National Cancer Institute (US); the second, by Queensland Cancer Fund and Queensland Health (Australia). Key results There was no information from either study on the e ects of screening on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 78 publications
1
51
0
8
Order By: Relevance
“…The most common histologic subtype of CMM, superficial spreading melanoma, is relatively slow-growing and has an in situ growth phase before becoming invasive, whereas the second most common type, nodular melanoma, is fast-growing and usually invasive at diagnosis [40]. Elsewhere, screening programs for CMM in the general population have implied rising incidences, but not turned out to be efficient, in terms of reducing mortality, for example in Germany [41] and other countries [42]. The marked association between elevated stage I CMM diagnosis and lower small-area deprivation shown in our results were probably affected by disparities in peoples' awareness and demand on health.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…The most common histologic subtype of CMM, superficial spreading melanoma, is relatively slow-growing and has an in situ growth phase before becoming invasive, whereas the second most common type, nodular melanoma, is fast-growing and usually invasive at diagnosis [40]. Elsewhere, screening programs for CMM in the general population have implied rising incidences, but not turned out to be efficient, in terms of reducing mortality, for example in Germany [41] and other countries [42]. The marked association between elevated stage I CMM diagnosis and lower small-area deprivation shown in our results were probably affected by disparities in peoples' awareness and demand on health.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Although recommendations to screen higher-risk individuals are made in some countries (Australia, New Zealand, Germany, the Netherlands and the UK [ 3 ]) national melanoma screening programs are not widely recommended (Germany, and pilots in Australia and the US [ 4 , 5 ]); and a recent Cochrane review (2019) determined that general adult screening of melanoma was not refuted by evidence [ 6 ]. Instead, the UK pursues education programs to raise awareness of signs and symptoms, risk factors and the need to self-check to promote earlier detection and thus reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the morbidity and mortality of malignant melanoma have increased significantly, with a high degree of malignancy [14]. It has been reported that uveal melanoma showed similar prognosis for Caucasian, Hispanic, Asian, and African American [15].…”
Section: Discussionmentioning
confidence: 99%